APPLICATION OF A PROTOCOL FOR PREVENTION OF PRESSURE ULCERS IN THE HOME CONTEXT: A TRAJECTORY COVERED - Geridice Lorna Andrade de Moraes; Cíntia Lira Borges; Edmara Teixeira Oliveira; Luana Rodrigues Sarmento; Patrícia Rebouças Araújo; Maria Josefina da Silva (Universidade Federal do Paraná, 2013)
The prevention of pressure ulcers is more efficient and economically viable than their treatment; hence there are standardized and normative protocols. This study's objective was to ascertain the influence of the application of a nursing protocol for the prevention of pressure ulcers in bed-bound older adults at home. This research was divided in two stages: the validation of content by specialist stomatherapy nurses and the clinical validation with elderly patients at risk of developing these risks to health. It was observed that the protocol is valid and that its reliability is attested in the aspects shown to be most important for the elderly population which is at risk for acquiring pressure ulcers